The Use of HbA1c in the Diagnosis of Type 2 Diabetes Mellitus among High Risk Group in Hospital Universiti Sains Malaysia - Ibrahim, Hasni (Japan International Cultural Exchange Foundation, 2009)
To improve the detection rate of type 2 diabetes, alternative approach to screening have been proposed, such as lower threshold for FPG or the use of HbA1c compared with OGTT, HbA1c measurement is quicker, more convenient, and avoids the need for fasting. Objectives: This study was conducted to evaluate the use of HbA1c as a diagnostic test for diabetes in high risk patient attending Outpatient Clinic at Hospital Universiti Sains Malaysia (HUSM) and to see whether HbA1c is a highly specific test and a convenient alternative to fasting plasma glucose (FPG) or 2-hour postprandial (2-hPP) for diabetes screening. Method: Measurement of FPG, 2-hPP and HbA1c level were performed in 200 subjects, aged 35 years and above with capillary blood glucose ≥ 5.6 mmol/L. The subjects also have at least one cardiovascular risk factor. Results: The mean age and body mass index for study sample were 52.4±9.6 and 26.7±5.0 respectively. The mean of FPG level was 5.7±2.3 mmol/dL, mean of 2-hPP level was 10.0±5.3 mmol/dL and HbA1c level was 6.1 ± 1.5%. Of 200 patients, 40.0% (n = 80) was diagnosed as normal glucose tolerance, 25.5% (n = 51) had impaired fasting glucose and/or impaired glucose tolerance and 34.5% (n = 69) had type 2 diabetes mellitus. The HbA1c of 7.0% gave an optimal sensitivity of 82% and specificity of 91% to predict a FPG " 7.0 mmol/dL. Whereas, HbA1c of 6.4% with sensitivity and specificity of 68% and 87% respectively was an optimal value to predict 2-hPP ≥ ll.lmmol/dL. All together, an HbA1c of 6.4% gave an optimal sensitivity of 68% and specificity of 89% to predict both FPG ≥ 7.0 mmol/dL and/or 2-hPP ≥ ll.lmmol/dL. Conclusion: HbA1c has good sensitivity and specificity to diagnose abnormal glucose tolerance and types 2 diabetes mellitus.